Hydrogeochemical assessment of termal water in fractured rocks – a Portuguese case study - Antunes, Isabel Margarida Horta Ribeiro (2017)
The thermal Fadagosa-Nisa water is located at north Alentejo (Portugal) and it is important in the economy of this region. The studied area is in a predominantly fractured granite and the water circulation is characteristic of fissured media, with a productivity of 2 L/s from a single well. Water hydrogeochemistry results revealed a mineralized water, with an electrical conductivity of 454 µS/cm and a total mineralization of 310 mg/L, neutral (pH=7.9-8.0) and a temperature of 19ºC. The thermal water has a dominant hydrogeochemical sodium-bicarbonate facies, with a fluoride (F-=9.6 mg/L) and hydrogen sulphide content (HS=15.2 mg/L), and moderate amounts of silica (SiO2=34.0 mg/L). The low nitrate (NO3-=0.1 mg/L) and sulphate (SO42-=1.6-5.2 mg/L) contents support the low vulnerability associated to the groundwater catchment. No significant seasonal changes have been found in the Fadagosa-Nisa thermal groundwater composition, suggesting a hydrogeochemical stability to the area. The regular hydrogeochemical results is in accordance to the low vulnerability obtained by the application of DRASTIC index in the Fadagosa-Nisa area.